2014
DOI: 10.4304/jltr.5.6.1256-1262
|View full text |Cite
|
Sign up to set email alerts
|

Types and Attributes of English Writing Errors in the EFL Context—A Study of Error Analysis

Abstract: Abstract-This study seeks to explore five 6 th grade EFL learners' major writing problems by analyzing the nature and distribution of their writing errors and it also investigates factors that cause errors in their writing in English through email communication. This study examined EFL learners' writing samples and followed taxonomy: grammatical, lexical, semantic, mechanics, and word order types of errors. Findings showed that participants made more mistakes on interlingual/transfer errors than on intralingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 16 publications
7
34
3
1
Order By: Relevance
“…The results of this study are consistent with the results of several studies like Sarfraz (2011), Ridha (2012), Karim et al (2015), and Alhaysony (2012) in that students made several types of errors related to different sources, such as interlingual and intralingual. The results of the studies of Tahaineh (2010) and Wu and Garza (2014) contradicted with the results of the current study in that they identified the main source of committing errors as interlingual; students use their knowledge of the first language in learning the second language.…”
Section: Resultscontrasting
confidence: 99%
“…The results of this study are consistent with the results of several studies like Sarfraz (2011), Ridha (2012), Karim et al (2015), and Alhaysony (2012) in that students made several types of errors related to different sources, such as interlingual and intralingual. The results of the studies of Tahaineh (2010) and Wu and Garza (2014) contradicted with the results of the current study in that they identified the main source of committing errors as interlingual; students use their knowledge of the first language in learning the second language.…”
Section: Resultscontrasting
confidence: 99%
“…Additionally, they tended to omit the main verb and prepositions necessary for the sentence structure. Wu and Garza (2014) also looked into the types and attributes of English written errors through the emails produced by the learners in the EFL context within the taxonomy of grammar, lexis, semantics, mechanics, and word order. It was revealed that most written errors were based on the interlingual errors rather than intralingual or developmental errors.…”
Section: Previous Studies Regarding Written Errors Made By Efl Learnersmentioning
confidence: 99%
“…Further, it was also found that they often made errors regarding voice as well as morphology such as converting nouns into plural forms (Chan, 2010;Jung, 2006). Additionally, it was also shown that they made frequent errors in subject and verb agreement (Wu & Garza, 2014;Zawahreh, 2012). As Chan (2010) noted, these errors commonly made by EFL learners might be attributed to their first language as it entails different linguistic aspects from English. Despite EFL language teachers' efforts to provide grammar lessons with corrective feedback for learners' writing, they experience difficulty especially in teaching English writing due to the grammatical aspects.…”
mentioning
confidence: 99%
“…Second, we should give a definition of a run-on sentence: 'a sentence containing two or more clauses not connected by the correct conjunction or punctuation' (Run-on sentence, n.d.). This error has been found frequently in both native (Connors & Lunsford, 1988;Lunsford & Lunsford, 2008) and nonnative (Hinkel, 2011;Sun, 2014;Wu & Garza, 2014) speakers' writing.…”
Section: Developmentmentioning
confidence: 92%